Moderasi Beragama dalam Lingkungan Pendidikan Industri: Upaya Mencegah Radikalisme dan Menumbuhkan Toleransi - Afip Miftahul Basar (INC- Islam Nusantara Center, 2026)
Abstract Religious moderation is an approach to faith that emphasizes balance, tolerance, and anti-extremism in practicing religious teachings. In industrial education environments such as polytechnics—which produce human resources for strategic national sectors—religious moderation values are crucial to preventing radicalism and fostering social harmony. This article aims to examine the role of Islamic religious education in instilling moderate attitudes among students in industrial vocational education. Using a qualitative approach through literature studies and contextual observation, the author finds that integrating religious moderation values into the curriculum and campus culture can foster tolerant and inclusive character, as well as raise students’ awareness of the dangers of radical ideologies. The verse QS. Al-Baqarah: 143, which refers to Muslims as ummatan wasathan, serves as a significant theological foundation affirming that balance and justice are central to Islamic teachings. This study recommends strengthening the role of religious lecturers as agents of moderation and promoting collaboration among campus stakeholders in building a peaceful and productive religious atmosphere within industrial polytechnics. Moderasi beragama merupakan pendekatan keagamaan yang menekankan keseimbangan, toleransi, dan anti-ekstremisme dalam menjalankan ajaran agama. Di lingkungan pendidikan industri seperti Politeknik, yang mencetak sumber daya manusia untuk sektor strategis nasional, nilai-nilai moderasi beragama menjadi sangat penting untuk mencegah radikalisme dan menciptakan harmoni sosial. Artikel ini bertujuan untuk mengkaji peran pendidikan agama Islam dalam menanamkan sikap moderat di kalangan mahasiswa pendidikan vokasi industri. Melalui pendekatan kualitatif dengan studi pustaka dan observasi kontekstual, penulis menemukan bahwa integrasi nilai moderasi beragama dalam kurikulum dan budaya kampus dapat menumbuhkan karakter toleran, inklusif, serta meningkatkan kesadaran mahasiswa terhadap bahaya paham radikal. Dalil QS. Al-Baqarah: 143 yang menyebut umat Islam sebagai ummatan wasathan menjadi landasan teologis penting dalam menegaskan bahwa keseimbangan dan keadilan adalah inti dari ajaran Islam. Hasil kajian ini merekomendasikan penguatan peran dosen agama sebagai agen moderasi serta kolaborasi antar pemangku kepentingan kampus dalam membangun atmosfer keberagamaan yang damai dan produktif di lingkungan politeknik industri.